Simultaneous enhancement of charge generation quantum yield and carrier transport in organic solar cells. Issue 41 (24th September 2015) - Armin, Ardalan; Wolfer, Pascal; Shaw, Paul E.; Hambsch, Mike; Maasoumi, Fatemeh; Ullah, Mujeeb; Gann, Eliot; McNeill, Christopher R.; Li, Jun; Shi, Zugui; Burn, Paul L.; Meredith, Paul
Abstract : Bulk heterojunction (BHJ) organic solar cells and photodiodes require optimised active layer structures for both charge carrier photo-generation and extraction to occur efficiently. Abstract : Bulk heterojunction (BHJ) organic solar cells and photodiodes require optimised active layer structures for both charge carrier photo-generation and extraction to occur efficiently. The most efficient polymer:fullerene devices comprising narrow optical gap donor polymers invariably have a high fullerene fraction. In such circumstances photo-generated carrier extraction is compromised, as charge transport is often unbalanced with electron transport in the fullerene dominating. In this current work we study the high efficiency blend system poly(2, 5-{2-octyldodecyl}-3, 6-diketopyrrolopyrrole- alt -5, 5-{2′, 5′-di[thien-2-yl]thieno[3, 2- b ]thiophene}) (DPP–DTT):phenyl-C71 -butyric acid methyl ester (PC70 BM). We show that by manipulating the packing of the (DPP–DTT) chains, large hole mobilities >0.02 cm 2 V −1 s −1 can be obtained in a simple polymer-only diode. More importantly, when blended with PC70 BM in a 1 : 3 ratio the hole mobility was found to increase to 0.2 cm 2 V −1 s −1 . This is the first case of a polymer:fullerene solar cell where the charge carrier transport is limited by the electron mobility of the fullerene rather than the hole mobility of the donor material. Photophysical measurements reveal that the charge generation quantum yield is also enhanced when the DPP–DTT chains are optimally packed. The simultaneous improvement of the charge transport properties and charge generation quantum yield delivers an order of magnitude increase in the power conversion efficiency.